(untitled) (Journal of Organizational Psychology, 2020)
The literature reviewed suggests that personality traits associated with extroversion and empathy are predictors of success in project management. There is no evidence in the literature reviewed that suggests any relationship between Obsessive Compulsive Disorder (OCD) or some of its features with the effectiveness of project management, although it is possible that some of these behaviors are beneficial, the essential factor is that the individual has these behaviors in an egosyntonic way, which means that he / she is aware of these trends and the benefit he / she gets from them, that these are in accordance with the image he / she has of himself / herself and can effectively regulate them by avoiding any kind of cognitive dissonance.